Renal effects of venoms of Mexican coral snakes Micrurus browni and Micrurus laticollaris. (15th July 2020) - Braga, Jacqueline Ramos Machado; Jorge, Antonio Rafael Coelho; Marinho, Aline Diogo; Silveira, João Alison de Moraes; Nogueira-Junior, Francisco Assis; Valle, Melisa Bénard; Alagón, Alejandro; de Menezes, Ramón Róseo Paula Pessoa Bezerra; Martins, Alice Maria Costa; Feijão, Levi Ximenes; Monteiro, Helena Serra Azul; Jorge, Roberta Jeane Bezerra
Abstract: The Micrurus snake venoms mainly cause systemic complications, essentially neurotoxicity. Previous studies, however, have described that they are involved in the occurrence of acute kidney injury (AKI) in animal models. AKI pathogenesis in snakebites is multifactorial and involves immunological reactions, hemodynamic disturbances, and direct nephrotoxicity. The aim of this study was to compare the nephrotoxic effects of coral snake venoms from M. browni ( Mb V) and M. laticollaris ( Ml V) on the proximal tubular epithelial cell line (LLC-MK2) and isolated perfused kidney. Using an MTT assay, both venoms significantly reduced cell viability at higher concentrations (25–100 μg/mL). Ml V (10 μg/mL) increased the perfusion pressure (PP) at 60, 90 and 120 min, while the Mb V did it only at 90 and 120 min. Renal vascular resistance (RVR) decreased at 60 min and increased at 120 min with Mb V, but decreased at 60, 90 and 120 min with Ml V. Urinary flow (UF) alterations were not observed with Ml V, but Mb V elevated them at 90 and 120 min. Both venoms significantly decreased the glomerular filtration rate (GFR), %TNa +, %TK + and %TCl − levels as of 60 min of perfusion. Oxidative stress analysis revealed that both venoms behaved similarly, reducing glutathione and increasing malondialdehyde levels. Kidney injury is not usually described in clinical cases of Micrurus snakebites. However, the potential for nephrotoxicity should be considered in the overall picture of envenomation. Highlights: The nephrotoxic effects of Micrurus browni and Micrurus laticollaris snake venoms were investigated. Both venoms reduced renal epithelial cells viability at the highest tested concentrations. Both venoms induced functional alterations in the isolated rat perfused kidney. Both venoms reduced glutathione and increased malondialdehyde levels.